2019
DOI: 10.33086/bfj.v4i2.1358
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Regulasi Dan Kolaborasi Terhadap Literasi Keuangan Dalam Upaya Penerapan Financial Technology Pada Usaha Kecil Dan Menengah

Abstract: Financial Technology (Fintech) telah memberikan akses kepada banyak pihak yang tidak memiliki rekening bank untuk masuk ke sektor usaha formal. Penerapan Fintech terbukti mampu membuka akses yang lebih besar terhadap layanan jasa keuangan formal, mendorong pertumbuhan ekonomi, serta pembangunan inklusif dan berkelanjutan. Untuk mendukung penerapan Fintech di Indonesia, maka tujuan penelitian ini adalah mengetahui pengaruh regulasi dan kolaborasi terhadap literasi keuangan pada usaha kecil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
0
8
0
5
Order By: Relevance
“…We will also divide the analysis to before and during covid-19 pandemic because we believe the pandemic has brought many changes that require its own analysis (Andini, 2017) According to (Zhang et al, 2019) in their study claimed that in China, as P2P getting bigger, it had a negative effect on domestic bank loans. Almost similarly, (Herdinata & Kohardinata, 2019) found that the growth of P2P in Indonesia has a significant impact on bank loans for the MSME segment. However, given the current pandemic situations, not many studies have been conducted about the impact of P2P especially on small bank loans, which is the type of bank that will be the first to feel the disruption in performance, if any (Yudaruddin, 2010).…”
Section: Introductionmentioning
confidence: 84%
“…We will also divide the analysis to before and during covid-19 pandemic because we believe the pandemic has brought many changes that require its own analysis (Andini, 2017) According to (Zhang et al, 2019) in their study claimed that in China, as P2P getting bigger, it had a negative effect on domestic bank loans. Almost similarly, (Herdinata & Kohardinata, 2019) found that the growth of P2P in Indonesia has a significant impact on bank loans for the MSME segment. However, given the current pandemic situations, not many studies have been conducted about the impact of P2P especially on small bank loans, which is the type of bank that will be the first to feel the disruption in performance, if any (Yudaruddin, 2010).…”
Section: Introductionmentioning
confidence: 84%
“…The main challenge in designing financial innovations is to create superior products that can be accepted and seamlessly integrated into users' everyday payment system habits without altering their routines (Herdinata & Kohardinata, 2019). Financial technology has transformed how society conducts financial transactions, reducing high capital and operational costs.…”
Section: Wwwjournalmabisorg 108mentioning
confidence: 99%
“…The entire number of organizational shares held in financial institutions in the form of institutions is known as institutional ownership (Herdinata & Pranatasari, 2019). These organizations include banks, insurance businesses, and investment companies (Ulandari, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%